Comparison of clinical characteristics and outcomes of critically ill adults with SARS-CoV-2 infection during Delta and Omicron variant predominance periods: a single-hospital retrospective cohort study - Peter Chen; Isabel Pedraza; Neil Modi; Keerthana Sankar; Alexander Polyak; Michael P Directo; Lily R Johnson; Norling Kho; Sharon K Isonaka; Matthew E Modes (BMJ Open Respiratory Research, 2023)
Introduction Initial reports suggest the B.1.1.529 (Omicron) variant of SARS-CoV-2 causes less severe disease compared with the B.1.617.2 (Delta) variant, though more widespread vaccination contributed to these findings. Little is known about clinical characteristics and outcomes of patients with SARS-CoV-2 infection requiring intensive care during periods of Delta and Omicron variant predominance.Aim To examine and compare characteristics of critically ill adults with SARS-CoV-2 infection during periods of Delta and Omicron variant predominance.Methods We conducted a retrospective cohort study of critically ill adults with SARS-CoV-2 infection at one academic hospital in Los Angeles during Delta (15 July 2021–23 September 2021) and Omicron (21 December 2021–27 January 2022) predominance. Patient characteristics were compared between Delta-period and Omicron-period hospitalisations, overall and stratified by vaccination status.Results 79 adults required intensive care during the Delta predominance period and 116 during the Omicron predominance period. We found similar proportions of intensive care unit admissions occurring in fully vaccinated patients between the two periods, despite Los Angeles County data revealing an almost 60% increase in the proportion of SARS-CoV-2 hospitalisations occurring in fully vaccinated persons. There was no difference in the need for invasive mechanical ventilation (IMV). Among those who required IMV, the median duration of IMV was shorter overall (Delta=18 days; Omicron=8 days; p=0.006) and among unvaccinated persons (Delta=19 days; Omicron=8.5 days; p=0.018). Among unvaccinated persons, the median intensive care unit length of stay was shorter (Delta=12 days; Omicron=5 days; p=0.037) during Omicron predominance. There was no difference in the proportion of patients who died while hospitalised.Conclusions In this single-hospital study, critically ill patients with SARS-CoV-2 infection experienced less severe respiratory disease during Omicron predominance, likely due to reduced variant-specific virulence. Vaccination likely reduced development of critical illness in adults with SARS-CoV-2 infection during Omicron predominance.